Алелі гена Ppd-D1 у зразках колекції Aegilops tauschii і м’якої пшениці - Чеботар, Г.О.; Чеботар, С.В.; Бабенко, Д.О.; Моцний, І.І.; Щербань, А.Б.; Cивола, Ю.М. (Вiopolymers and Cell, 2012)
Light period significantly influences on the growth and development of plants. One of the major genes of photoperiod sensitivity is Ppd-D1, located on the chromosome 2D. The aim of the work was to determine the alleles and molecular structure of Ppd-D1 gene in samples from the collection of Ae. tauschii accessions, which have different flowering periods, and in 29 Ukrainian wheat varieties. Methods. We used methods of allele-specific PCR with primers to the Ppd-D1 gene, sequencing and Blast-analysis. Results. The collection of Ae. tauschii accessions and several varieties of winter and spring wheat was studied. The molecular structure of the allelic variants (414, 429 and 453 b. p.) of Ppd-D1b gene was determined in the collection of Aegilops. tauschii accessions. Conclusions. The Ppd-D1a allele was present in all studied varieties of winter wheat. 60 % of spring wheat is characterized by Ppd-D1b allele (size of amplification products 414 b. p.). Blast-analysis of the sequence data banks on the basis of the reference sequence of sample k-1322 from the collection of Ae. tauschii accessions has shown a high homology (80 to 100 %) between the nucleotide sequences of PRR genes, that characterize the A and D genomes of representatives of the genera Triticum and Aegilops. Keywords: Aegilops tauschii, bread wheat, allele-specific PCR, phd-D1. Світловий період суттєво впливає на ріст і розвиток рослин. Одним із головних генів чутливості до фотоперіоду є Ppd-D1 з родини PRR, розташований на хромосомі 2D. Мета роботи полягала у визначенні алельного стану і молекулярної структури гена Ppd-D1 у зразках з колекції Ae. tauschii з різними строками цвітіння та у 29 українських сортів м’якої пшениці. Методи. Алель-специфічна ПЛР з праймерами до гена Ppd-D1, секвенування і Blast-аналіз. Результати. Досліджено колекцію зразків Ае. tauschii та низку сортів озимої і ярої м’якої пшениці, визначено молекулярну структуру алельних варіантів (414, 429 і 453 п. н.) гена Ppd-D1b у колекції Ae. tauschii. Висновки. У досліджуваних сортів озимої м’якої пшениці присутній алель Ppd-D1a, а серед ярих сортів 60 % відрізняються наявністю алеля Ppd-D1b (розмір продуктів ампліфікації 414 п. н.). Blast-аналізом нуклеотидних послідовностей цього гена з банків даних у порівнянні з референсною послідовністю зразка k-1322 з колекції Ae. tauschii показано високий рівень гомології (від 80 до 100 %) між послідовностями генів PRR, характерних для геномів А і D представників родів Triticum і Aegilops. Ключові слова: Аеgilops tauschii, м’яка пшениця, алель-специфічна ПЛР, Ppd-D1. Световой период существенно влияет на рост и развитие растений. Одним из главных генов чувствительности к фотопериоду является Ppd-D1, расположенный на хромосоме 2D. Цель работы состояла в определении аллельного состояния и молекулярной структуры гена Ppd-D1 в образцах из коллекции Ae. tauschii с разными сроками цветения и в 29 украинских сортах мягкой пшеницы. Методы. Аллель-специфичная ПЦР с праймерами к гену Ppd-D1, секвенирование и Blast-анализ. Результаты. Исследована коллекция образцов Ае. tauschii и ряд сортов озимой и яровой мягкой пшеницы, определена молекулярная структура аллельных вариантов (414, 429 и 453 п. н.) гена Ppd-D1b в коллекции Ae. tauschii. Выводы. У исследованых сортов озимой мягкой пшеницы присутствует аллель Ppd-D1a, а среди яровых сортов у 60 % определен аллель Ppd-D1b (размер продуктов амплификации 414 п. н.). Blast-анализом нуклеотидных последовательностей этого гена из банков данных в сравнении с референсной последовательностью образца k-1322 из коллекции Ae. tauschii показан высокий уровень гомологии (от 80 до 100 %) между последовательностями генов PRR, характерных для Аи D-геномов представителей родов Triticum и Aegilops. Ключевые слова: Аеgilops tauschii, мягкая пшеница, алель-специфичная ПЦР, Ppd-D1.